Neuronal MHC-I complex is destabilized by amyloid-β and its implications in Alzheimer’s disease - Min-Seok Kim; Kwangmin Cho; Mi-Hyang Cho; Na-Young Kim; Kyunggon Kim; Dong-Hou Kim; Seung-Yong Yoon (Cell & Bioscience, 2023)
Abstract Backgrounds The expression of major histocompatibility complex I (MHC-I) in neurons has recently been shown to regulate neurite outgrowth and synaptic plasticity. However, its contribution to neurodegenerative diseases such as Alzheimer's disease (AD) remains largely unknown. Methods In this study, we investigated the relationship between impaired MHC-I-β2M complex and AD in vitro and human AD samples. Interaction between protein was identified by liquid chromatography-tandem mass spectrometry and confirmed by immunoprecipitation. Single-chain trimer of MHC-I-β2M was generated to study the effect of stabilization of MHC-I-β2M complex on NCAM1 signaling. Results MHC-I is destabilized in the brains of AD patients and neuronal cells treated with oligomeric β-amyloid (Aβ). Specifically, Aβ oligomers disassemble the MHC-I-β2-microglobulin (β2M) complex, leading to reduced interactions with neural cell adhesion molecule 1 (NCAM1), a novel interactor of neuronal MHC-I, and decreased signaling. Inhibition of MHC-I-β2M complex destabilization by non-dissociable MHC-I-β2M-peptide complex restored MHC-I-NCAM1 signaling in neuronal cells. Conclusions The current study demonstrated that disruption of MHC-1-NCAM1 signaling by Aβ induced disassembly of MHC-I-β2M complex is involved in the pathophysiology of AD. Moreover, our findings suggest modulation of MHC-I stability may be a potential therapeutic target for restoring synaptic function in AD.